Impact of Chemical and Alternative Fungicides Applied to Grapevine cv Nebbiolo on Microbial Ecology and Chemical-Physical Grape Characteristics at Harvest - Rantsiou, Kalliopi; Giacosa, Simone; Pugliese, Massimo; Englezos, Vasileios; Ferrocino, Ilario; Río Segade, Susana; Monchiero, Matteo; Gribaudo, Ivana; Gambino, Giorgio; Gullino, Maria Lodovica; Rolle, Luca (Frontiers in Plant Science, 2020)
Viticulture is a cropping system in which treatment against fungal diseases (in particular powdery and downy mildews) can be extremely frequent. Accordingly, a reduction in antimicrobial treatments and the application of environmentally-friendly compounds are becoming increasingly important for a more sustainable viticulture. In addition to their effect against pathogens, the impact of these products on the quality of the grapes is very important for the oenological industries, but unfortunately at present few data are available. We evaluated the effect of the application of biocontrol products and resistance inducers in the vineyard on the mechanical properties, microbial ecology, technological and phenolic maturity of Vitis vinifera ‘Nebbiolo’ grapes at harvest. The yield and vigour of vines were not influenced by the treatments, nor were the production of primary and secondary metabolites. However, the active ingredients influenced the mechanical properties of the skin (hardness and thickness). A significant hardening of the skin was detected when laminarin and chito-oligosaccharides were used, and sulphur induced a thickening of the skin with potential consequences for wine quality. Furthermore, the yeast community present on grape berries was influenced by the treatments. The abundance of Aureobasidium pullulans, the dominant species on the grape berry, changed in response to the compounds used. In addition, Alternaria sp. was reduced in some treatments with a potentially positive effect on the quality and the safety of the grapes. This study provides an overview of the effect of biocontrol products and resistance inducers on microbial ecology and ‘Nebbiolo’ grape quality, contributing to the establishment of more sustainable and effective defence strategies in viticulture.